The Impact of Human Resource Practices on Employee Job Satisfaction in Ground Handling Agencies of Pakistan - Abdul Ahad; Hamza Akram; Muhammad Inam (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2021)
The focus of this research was on “The Impact of HR Practices on Employee Job Satisfaction”. The purpose of research was to study the impact of various Human resource practices on employees’ job satisfaction. Secondary data was gathered through library and Internet searches of literature. Questionnaires were used to collect the primary data. The data was analyzed using SPSS software for frequencies, regression parameters, and cross tabulation. Statistics concepts were used to interpret the results. A sample size of 150 people who were requested to fill out questionnaires based on their overall job experience in various Ground Handling Agencies of Pakistan. The targeted Ground Handling Agencies whom data is collected are Shaheen Airport Services, Dnata Ground Handling, PIA and Menzies Aviation. The findings suggested that the reward system and promotion practices have a significant impact on the job satisfaction of employees of Ground Handling Agencies/companies. When more incentives and promotion opportunities are provided on monthly or yearly basis respectively to employees the more satisfied, they are with their jobs